Optimasi Kadar Aspal pada Stabilisasi Tanah Pasir Menggunakan Aspal dengan Uji CBR - Ika Ernawati, Willis Diana , Afriza Marianti , (Semesta Teknika, 2011)
This research aims to determine the optimum bitumen content for sandy soil stabilization (sandy soil obtained from Glagah beach, Kulon Progo). Variation in bitumen content being used was 0% to 5% by weight of dry soil. Against, a mixture of bitumen and sandy soil proctor compaction tests was performed to obtain optimum moisture content (OMC) mixture which then was tested its California Bearing Ratio (CBR). The addition of bitumen content in soil stabilization with bitumen causing a continuing lack of OMC (Optimum Moisture Content) and increased MDD (Maximum Dry Density) on the compaction process. The maximum CBR value, 20%,Â  was obtained at 2% bitumen content. . There was an increase of 150% CBR value when compared with the original soil without stabilization. CBR tends to decrease with further increase of the bitumen contentÂ  up to 5% which may due to the mixture being more plastic.